Dinamika Otonomi Tubuh Perempuan: Antara Kuasa dan Negosiasi atas Tubuh - Benedicta, Gabriella Devi (Masyarakat: Jurnal Sosiologi, 2011)
This paper discusses sexuality and autonomy of woman’s body through a study of sexy dancers in entertainment industry in Malang, East Java. Entertainment industry, including night club industry is capital manifestation and a contested arena of any kind of ideology like capitalism and patriarchy. However, a woman still can show her autonomy of her body instead of being a commodity object. She can make her body as a subject. In this case, she, herself, becomes a doer which is controlling her own body. The dynamic of woman’s authority of her body is influenced by a certain setting and context. It can be seen in social relation involved sexy dancers and other actors. She can have high bargaining position and negotiation of her body when she relates to a certain actor, but on the other side she may not have an autonomy of her body when she relates to another actor. The autonomy of her body is multi dimension and not absolute.